Literature Review: Quarantine and Lockdown During Covid19 Outbreak Impact on Mental Health Problem - Dea Rosa Gracia; Erica Rosa Rubetta (JURNAL KESEHATAN LINGKUNGAN, 2020)
Introduction: COVID-19 is a unique disease that was first confirmed in Wuhan, Wubei, China in late 2019 and within 6 months the virus spread rapidly throughout the world. The obscurity in overcoming this virus is the background of the interventions applied. Several interventions conducted, such as nationwide lockdowns, quarantine and isolation. In addition to avoid the virus transmission, these interventions also have psychological impacts that affect the mental health. Methods: We did a review of the mental health outcomes referring to several interventions amid COVID-19 outbreak using two databases. Out of 302 papers found by the search engine, 5 articles were counted in this review. Discussion: Most reviewed researches proclaimed adverse mental health problems, along with anxiety, stress, and post-traumatic stress disorder. Stressors consist of infection fears, grieves, boredom, stigma, faulty information, short sleep duration, and minimum social activities. Several researchers have proposed abiding effects. Conclusion: Social interventions which are imposed limit the process of meeting the needs of human life. It is crucial to point out the mental health of the population and take charge to diminish its adverse effects for the time being. Therefore, the Government needs to implement a strict and fair policy, especially on the issue of community survival. Public health protocol socialization needs to be done, especially in controlling the transmission of viruses in public places, such as malls, public transportations, schools, workplaces, and many other.